Essai de domestication de Mangobo (PFNL) Sclerosperma mannii Wendl « Syn. S. dubiumBecc » par voie générative dans les conditions de Bengamisa, RD. Congo - MASIYA, P. KOMBE LIBENGE; BITIKA, J. ABAYA; J. NLANDU THUBI; A. L. OKUNGO (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2021)
A test of reproduction and plantation of « Mangobo » Sclerosperma manii wendl was undertaken at ISEA/Bengamisa. The seedling of 100 seeds in gemoir produced 65 plantules that has been put in place to the spacings of (4 x 3) m The maximal values calculated of the germination rate, energy germinative and speed of germination were the respective order of 65, 60 and 58%, the rates of survival of the plantules were of 97% after 12 months of observation. The plantules showed a middle growth in height of 56cm with a middle production of leaves by foot to the term of the test.